Bone Tissue Engineering via Carbon‐Based Nanomaterials. Issue 5 (24th January 2020) - Peng, Zhili; Zhao, Tianshu; Zhou, Yiqun; Li, Shanghao; Li, Jiaojiao; Leblanc, Roger M.
Abstract: Bone tissue engineering (BTE) has received significant attention due to its enormous potential in treating critical‐sized bone defects and related diseases. Traditional materials such as metals, ceramics, and polymers have been widely applied as BTE scaffolds; however, their clinical applications have been rather limited due to various considerations. Recently, carbon‐based nanomaterials attract significant interests for their applications as BTE scaffolds due to their superior properties, including excellent mechanical strength, large surface area, tunable surface functionalities, high biocompatibility as well as abundant and inexpensive nature. In this article, recent studies and advancements on the use of carbon‐based nanomaterials with different dimensions such as graphene and its derivatives, carbon nanotubes, and carbon dots, for BTE are reviewed. Current challenges of carbon‐based nanomaterials for BTE and future trends in BTE scaffolds development are also highlighted and discussed. Abstract : Carbon‐based nanomaterials demonstrate enormous potential in bone tissue engineering (BTE) to treat critical‐sized bone defects due to their superior properties. Recent advancements of different dimensional carbon‐based nanomaterials (i.e., graphene oxide, carbon nanotubes, and carbon dots) in BTE are presented. Current challenges of BTE applications with carbon‐based nanomaterials and future trends of BTE are also highlighted and discussed.